(untitled) (Fiep Bulletin - online, 2014)
The MUNICIPAN proposed rethink our society and human values so essential in our daily life. Discussed is a management model of society in which winning at any cost is not the best way out, but ensure the fellowship, justice and honesty on the ethics. Disseminate the MUNICIPAN is the general objective of the study, reporting the inclusion, elucidating the concern of the 6th CRE making the Pan-American and Para Pan-American Games. It is important to show the benefits of Physical Education and the MUNICIPAN, whose inclusive nature is present in the project, the socialization and humanization of the children who attended the MUNICIPAN, leading students to realize as part of society, living the perception, social values, minimizing the risk and the social dropout. Congress has been made based on “MultiEducação” and PCNs for the Physical Education, seeking support for the practical aspects-working as integrators and promoters in the practice of Physical Education, contributing to citizenship, independence, cooperation, social participation, saying democratic values and principles. The study is a qualitative and descriptive for collecting data. It used the technique of Geometry allegory of the animals, Postic (1993), and Gheerbrant & Chevalier (1999), whose symbolism of the Mascot complements this study in the language of Imaginary Social. The sample intentional second Gil (1987), is composed of professionals 6th CRE and Physical Education, with 550 students of both sexes, between 4 and 17 years in 58 schools. The games were held with ten modalities divided into five categories. The dolphin that was the mascot of the games MUNICIPAN, symbol of regenerate action, divination, wisdom and prudence related to the students, symbolizes the change, transformation, knowledge and socialization, with wisdom and prudence win its limits, outweighing obstacles and devote themselves heroes. The symbolism of dolphins in the municipal Coat represents the Rio de Janeiro.